Adult Congenital Heart Disease - Moodie, Douglas S. (Ochsner Clinic, L.L.C. and Alton Ochsner Medical Foundation, 2002)
One million people over the age of 20 suffer from congenital heart disease in the United States. These adult patients can slip through the cracks of our medical system; many are too old to be cared for in most pediatric institutions by pediatric cardiologists and, unfortunately, most adult cardiologists are not trained in congenital heart disease. Therefore, it is important to identify the common lesions in adult congenital heart disease and how they should be managed. Acyanotic congenital heart disease in the adult population primarily involves left-to-right shunts, such as atrial septal defect, patent ductus arteriosus, and obstructive lesions such as aortic coarctation of the aorta. The most common form of cyanotic congenital heart disease in adults is tetralogy of Fallot. Other complex conditions seen in adults include univentricular hearts, Ebstein's anomaly of the tricuspid valve, and corrected transposition of the great vessels. Most patients with congenital heart disease will need to undergo surgery, catheterization, or catheterization intervention. Results are excellent in the adult population. Long-term follow-up is needed for any adult congenital heart patient receiving care in institutions that are well organized and well equipped, as we learn more about the natural and unnatural history of these conditions.